2013
DOI: 10.2139/ssrn.2369898
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Debt Across Euro Area Countries: The Role of Individual Characteristics, Institutions and Credit Conditions

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…Institutional differences across countries are also important. In particular, Bover et al (2016) show that in countries with longer repossession periods, the percentage of people who borrow is smaller, the youngest group of households borrow lower amounts (conditional on borrowing), and mortgage interest rates paid by low-income households are higher. Table 1 also provides a first glimpse at the prevalence of fixed versus adjustable mortgage rates.…”
Section: Datamentioning
confidence: 97%
“…Institutional differences across countries are also important. In particular, Bover et al (2016) show that in countries with longer repossession periods, the percentage of people who borrow is smaller, the youngest group of households borrow lower amounts (conditional on borrowing), and mortgage interest rates paid by low-income households are higher. Table 1 also provides a first glimpse at the prevalence of fixed versus adjustable mortgage rates.…”
Section: Datamentioning
confidence: 97%
“…inability of many consumers to make optimal financial investments. Some evidence of this reality is the acquisition of complex financial products, such as preferred stocks, by groups of consumers with an inappropriate investor profile, as well as the excessive debt levels of many low-income households (Bover, Casado, & Costa, 2014). The increasing complexity of financial assets currently offered by the capital markets requires small investors to be financially qualified in order to make well-informed decisions that maximize their economic well-being.…”
mentioning
confidence: 99%
“…Magri (2007) identified that although self-employed workers have a greater tendency of applying for credit, they are more likely to be rationed by lenders. Bover et al (2014) state that being employed is associated with a higher likelihood of holding secured debt. Henderson and Scobie (2009) reported that those who were unemployed or out of the labour force had lower levels of debt than those who were in employment.…”
Section: Employment Statusmentioning
confidence: 99%